Cerebral palsy in adolescence: results from a research (Psicologia USP, 2009)
It is very important to study self-concept, coping and mental health in adolescents suffering from Cerebral Palsy. This population has been rarely studied. Besides, these variables can contribute to the adaptation of these youth that face very adverse conditions, and can be protective and risk factors to their psychological health. We studied a sample of 78 subjects suffering from Cerebral Palsy (aged between 12 and 19 years old). We found the following results: a) girls show higher levels of psychopathology than boys, b) with age, the values of self-concept are lower and the values of non active coping are higher, c) some types of diagnosis of Cerebral Palsy differentiate themselves by the self-concept, d) self-concept correlates negatively with all indexes of psychopathology, e) non active coping correlates negatively with anxiety and some indexes of psychopathological symptomatology from BSI.